Communication in Muslim nations - Hussain, Mohd. Yusof (IIUM Press, International Islamic University Malaysia, 2008)
This book is a compilation of thirteen essays. The Muslim nations covered are Indonesia, Malaysia, Brunei darusslaam, Pakistan and Bosnia. The communication media covered are newspapers, magazines, radio, television, audio cassettes, compact discs, the internet and word of mouth. Most of the discussions focus on the present. However, there is a special chapter discussing communication practices in early Islam. The book concludes with a chapter on the role of the mosque as a centre of religious communication.